2024
DOI: 10.1002/anie.202402086
|View full text |Cite
|
Sign up to set email alerts
|

From Cd(SCN)2(CH4N2S)2 to Cd(SCN)2(C4H6N2)2: Controlling Sulfur Content in Thiocyanate Systems Significantly Improves the Overall Performance of UV Nonlinear Optical Materials

Yuwei Kang,
Can Yang,
Jie Gou
et al.

Abstract: Combining a strong second‐order nonlinear optical (NLO) effect (>1×KH2PO4 (KDP)), a large bandgap (>4.2 eV), and a moderate birefringence in ultraviolet (UV) NLO crystals remains a formidable challenge. Herein, Cd(SCN)2(C4H6N2)2, the first example of a thiocyanate capable of realizing a phase‐matched UV NLO crystal material, is obtained by reducing the sulfur (S) content in the centrosymmetric (CS) structure of Cd(SCN)2(CH4N2S)2. Compared to the "shoulder‐to‐shoulder" one‐dimensional (1D) chain of Cd(SCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Nonlinear-optical (NLO) materials with short cutoff edges that can convert laser frequency to the ultraviolet (UV) and even deep-UV regions through a second-harmonic-generation (SHG) process play a vital role in laser precision machining, remote sensing, lithography, and other fields, so as to become research hotspot in the NLO realm. Despite significant efforts being invested in the design and synthesis of short-wavelength NLO materials, further advancement is still needed for optimal performance. Crystallization into a noncentrosymmetric (NCS) space group is the foremost condition, and certain strategies have been implemented to enhance the probability of obtaining NCS structures. Combining local asymmetric units during synthesis has been proven to be effective in producing new NCS materials. , Nevertheless, asymmetric building units may arrange antiparallel and result in centrosymmetric (CS) structures.…”
mentioning
confidence: 99%
“…Nonlinear-optical (NLO) materials with short cutoff edges that can convert laser frequency to the ultraviolet (UV) and even deep-UV regions through a second-harmonic-generation (SHG) process play a vital role in laser precision machining, remote sensing, lithography, and other fields, so as to become research hotspot in the NLO realm. Despite significant efforts being invested in the design and synthesis of short-wavelength NLO materials, further advancement is still needed for optimal performance. Crystallization into a noncentrosymmetric (NCS) space group is the foremost condition, and certain strategies have been implemented to enhance the probability of obtaining NCS structures. Combining local asymmetric units during synthesis has been proven to be effective in producing new NCS materials. , Nevertheless, asymmetric building units may arrange antiparallel and result in centrosymmetric (CS) structures.…”
mentioning
confidence: 99%
“…Crystals with second harmonic generation (SHG) effects in the field of nonlinear optics (NLO) hold significant importance, due to their ability to precisely manipulate light and generate coherent radiation at various wavelengths. This characteristic finds extensive applications in high-resolution microscopy imaging, precision manufacturing, lithography, and optical communication. Consequently, the pursuit of frequency doubling crystals with exceptional performance has become a focal point for the scientific and application community. However, the commercial frequency doubling crystals are limited to minority examples, including AgGaS 2 (AGS), ZnGeP 2 (ZGP), LiB 3 O 5 (LBO), KH 2 PO 4 (KDP), KTiOPO 4 (KTP), KBe 2 BO 3 F 2 (KBBF), and β-BaB 2 O 4 (β-BBO). Hence, primitive exploration of new frequency doubling crystal materials remains an urgent research task. …”
mentioning
confidence: 99%
“…As previously mentioned, substituting heteroatoms presents an excellent strategy for obtaining high-performance NLO crystals. We have found that replacing O with S atoms having high polarizability is particularly favorable for achieving larger effects in NLO oxysulfide crystals. , Additionally, controlling the sulfur content is also very important, because it contributes to structural transformation and enhances the SHG effect, which can be exemplified by Wu et al’s work (from Cd(SCN) 2 (CH 4 N 2 S) 2 to Cd(SCN) 2 (C 4 H 6 N 2 ) 2 ) . Besides, from the structural perspective, O and S show distinct electronegativity and bonding characteristics; hence, their combination can construct novel functional units, further resulting in interesting crystal structures and optical performances.…”
mentioning
confidence: 99%